Decision aids in patients with osteoporosis: A scoping review - Yanyu Fang; Qin Jia; Yaqin Dai; Siqi Li (PLoS ONE, 2025)
Introduction Although various methods exist for osteoporosis prevention, most patients fail to receive optimal treatment due to information asymmetry between physicians and patients, as well as limited consultation time. Current literatures suggest that decision aids can support clinical decision-making by improving patients’ risk perception and treatment acceptance. Objective This scoping review described the use and effectiveness of decision aids in clinical decision-making among individuals with osteoporosis. Inclusion criteria The review will include studies conducted in various countries that focus on decision-aiding interventions for people with osteoporosis in different settings and are published in English or Chinese. Methods PubMed, CINAHL, Web of Science, Embase, Cochrane Library, China Knowledge Network, Wanfang Database, and China Biomedical Literature Database were searched. The search timeframe was from the establishment of the database to June 30, 2024. Studies that meet the inclusion criteria will be eligible for selection. The process of selecting eligible studies will then be summarized on a PRISMA-ScR chart. Collated in data-extraction tables will be authorship information, publication date, country, study site, sample information, study type, intervention form, content elements, application scope, and outcome indicators. The content elements, application scope, and outcome indicators will be analyzed using a thematic analysis and summarized using a narrative summary. Conclusion With strong efficacy and viability, DA greatly enhances patients’ decision-making experience and decision quality. In order to provide patients with osteoporosis with high-quality decision-making support, it will be necessary to conduct large-scale, randomized controlled studies in the future with the goal of guaranteeing homogeneous interventions, expand the scope and meaning of the application of DA in osteoporosis, improve professional support during the decision-making process, create scientific and useful decision-making aids, and take specific actions.